2019
DOI: 10.1080/00223980.2019.1567453
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Workplace Incivility and Helping Behavior: Roles of Job Dissatisfaction and Political Skill

Abstract: This article investigates the mediating role of job dissatisfaction in the relationship between employees' perceptions of workplace incivility and their helping behavior, as well as the buffering role of political skill in this process. Three-wave, time-lagged data collected from employees and their supervisors revealed that employees' exposure to workplace incivility diminished their helping behavior through their sense of job dissatisfaction. This mediating role of job dissatisfaction was less salient, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 91 publications
4
35
0
2
Order By: Relevance
“…Such behaviors are characteristically rude and discourteous, displaying a lack of regard for others" (Andersson & Pearson, 1999, p. 457). While less intense than workplace harassment or violence, WPI is prevalent in organizations, and has been shown to be negatively linked to performance (Mao et al, 2019), helping behavior (De Clercq et al, 2019), and positively linked to absenteeism (Sliter et al, 2012) and turnover intentions (Lim et al, 2008).…”
mentioning
confidence: 99%
“…Such behaviors are characteristically rude and discourteous, displaying a lack of regard for others" (Andersson & Pearson, 1999, p. 457). While less intense than workplace harassment or violence, WPI is prevalent in organizations, and has been shown to be negatively linked to performance (Mao et al, 2019), helping behavior (De Clercq et al, 2019), and positively linked to absenteeism (Sliter et al, 2012) and turnover intentions (Lim et al, 2008).…”
mentioning
confidence: 99%
“…Second, this study highlights the usefulness of the curvilinear relationship model. Although existing studies have treated OCB and instigated incivility as outcome variables of experienced incivility, most have only considered a one-dimensional relationship involving decreased OCB and increased instigated incivility (De Clercq et al , 2019; Cortina et al ., 2017; Schilpzand et al ., 2016; Porath and Erez, 2007). These studies relied intrinsically on the interpretations of the conservation motive of the COR theory or on similar logic.…”
Section: Discussionmentioning
confidence: 99%
“…What is helping behavior? Since its inception, helping behavior has received a substantial amount of scholarly attention due to its strong impact on overall company performance (De Clercq et al, 2019a). In general, helping behavior represents helping a coworker with task-related issues (Organ et al, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other words, social exchange theory specifies costs and rewards that drive people's decisions and behaviors in a relational context (Cortez and Johnston, 2020). Extending the basic premise of social exchange theory, prior research has shown that helping behavior exhibited by an employee is governed by how much help that he or she has received from coworkers, and/or whether an employee believes that coworkers will reciprocate help in the future (De Clercq et al, 2019a;Golden and Veiga, 2018;Yang et al, 2018). Although social exchange theory has been commonly applied to the study of helping behavior based upon employee-to-employee relationships, the exchange relationship between a leader and an employee can also determine the extent of helping behavior exhibited by the employee (Carnevale et al, 2019;Hirst et al, 2016;Randel et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%